Assessment of arsenic contamination in the Red river: high resolution monitoring coupled with spatial analysis by GIS - Ha, Dang Thi; Alexandra Coynel,; Cecile Grosbois, (Vietnam Journal of Science and Technology, 2018)
The Red River (China/Vietnam, A = 155 000 km2) is a typical humid tropics river originating from the mountainous area of Yunan Province in China. Based on two sampling campaigns covering the whole Vietnamese watershed in 40 sites at low and high water levels during 2009, the seasonal and spatial variations of As concentrations in dissolved and particulate phases were determined. The dissolved As concentrations in rainy season were relatively lower than in dry season, suggesting the dilution effect of less arsenic-contaminated water. In contract, the particulate As concentrations during low water level were clearly lower than that during high water level, demonstrating a change phenomenon in As source(s) with hydrology. In addition, in order to assess spatial distribution of the As contamination in the Red River watershed and localize geochemical anomalies, multidimensional statistical analyses combined with As maps generated by GIS tool were used. The results showed that the highest As concentrations are originated from the upstream catchment and strongly decrease from upstream to downstream. Finally, the comparison between dissolved As concentrations from the Red River watershed and the national technical regulation on surface water (QCVN 08:2008/BTNMT) indicated that the quality of water in the Vietnamese Red River watershed can be classified as poor quality in the upstream part and as mediocre quality in the downstream part.